Preparation and characterization of PAM/SA tough hydrogels reinforced by IPN technique based on covalent/ionic crosslinking. Issue 4 (5th September 2014) - Li, Yali; Wang, Chaoxia; Zhang, Wan; Yin, Yunjie; Rao, Qingqing
ABSTRACT In order to fabricate tough hydrogels with superior formability, polyacrylamide/sodium alginate (PAM/SA) interpenetrating polymer network (IPN) hydrogels were produced with ionically crosslinked SA interpenetrated in covalently crosslinked PAM. TGA results show that the heat resistance of PAM/SA IPN hydrogel is improved as compared to that of the individual component. Swelling studies indicate that increasing either chemical crosslinker content or ionic crosslinking via adding more N, N′‐methylenebisacrylamide (MBA) or SA results in lower ESR. It is concluded by tensile test that loosely crosslinked PAM coupled with tightly crosslinked SA improve mechanical strength for hydrogels based on covalent/ionic crosslinking. PAM/SA hydrogels via "one‐pot" method can form different complex shapes with mechanical properties comparable to conventional double network (DN) gels. The fracture strength of PAM0.05/SA20 reaches level of MPa, approaching 2.0 MPa. The work strives to provide method to tune mechanical and physical properties for hydrogels, which is hopefully to guide the design of hydrogel material with desirable properties. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41342.